Expression of vimentin protein and neurofilament on forelimb buds of black-6 mice on gestation day 12 induced by 2-methoxyethanol by RT-PCR - YULIA IRNIDAYANTI (Nusantara Bioscience, 2010)
Abstract. Irnidayanti Y. 2010. Expression of vimentin protein and neurofilament on forelimb buds of black-6 mice on gestation day 12 induced by 2-methoxyethanol by Real-Time RT-PCR. Nusantara Bioscience 2: 116-120. The aim of this study was to investigate impact of 2-methoxyethanol, a major industrial chemical of plastic. Gene expression analysis is increasingly important in biological research, while real-time reverse transcription PCR (RT-PCR) is becoming the method of choice for high-throughput and accurate expression profiling of selected genes. Pregnant black-6 mice were injected intraperitoneally to 7.5 mmol/kg of 2- methoxyethanol on gestation day (GD) 10. Embryo was obtained on gestation day 12. Forelimb buds of embryo were collected and then put in the tube, which containing RNA-latter solution. To identify gene expression changes in forelimb bud caused induction 2-methoxyethanol, Real-Time PCR was used in this research. For the experiments, the real-time RT-PCR Light Cycler technology was used. The results suggested that injection of 2- methoxyethanol, in prenatal period especially on gestation day 12, the expression of vimentin in forelimb buds of mice treatment increase than control mice. Meanwhile, the expression of neurofilament tended to decrease, indirectly is not caused by the injection of 2- methoxyethanol.